Influence of ethanol-blended B7-diesel on in-cylinder combustion characteristic, engine thermal efficiency and emission of a 3L-compression ignition engine - Teerapat Suteerapongpun; Poonnut Thaeviriyakul; Watanyoo Phairote; Peerawat Saisirirat; Watcharin Po-ngaen; Hidenori Kosaka; Preechar Karin (Applications in Energy and Combustion Science, 2026)
This study investigated the effects of blending weight ratio of 5% and 10% ethanol (B7E5 and B7E10) with standard B7-diesel on the performance, combustion, and emission characteristics of a light-duty common-rail diesel engine. The engine was tested on a dynamometer across various speeds (1600–2000 rpm) and loads (84 and 112 Nm) to analyze in-cylinder pressure, thermal efficiencies, and exhaust emissions. Results indicated significant emission benefits, especially at high loads. The B7E10 blend reduced smoke intensity by approximately 75% and carbon dioxide emissions by 34% compared to the baseline B7. The performance analysis revealed a critical trade-off associated with the ethanol blends: while the inherent oxygen content in ethanol significantly improved the indicated thermal efficiency (ITE) through enhanced combustion, its lower viscosity simultaneously led to increased frictional losses. Consequently, these competing effects resulted in only a modest improvement in brake thermal efficiency (BTE) and comparable brake-specific energy consumption (BSEC) compared to the baseline B7. The primary objective is to identify the benefits and trade-offs associated with ethanol blending in biodiesel-based diesel fuels that are compatible with existing diesel vehicles. • This study investigated the effects of blending weight ratio of 5% and 10% ethanol (B7E5 and B7E10) with standard B7-diesel on the performance, combustion, and emission characteristics of a light-duty common-rail diesel engine. • The B7E10 blend reduced smoke intensity by approximately 75% and carbon dioxide emissions by 34% compared to the baseline B7. • The performance analysis revealed a critical trade-off associated with the ethanol blends: while the inherent oxygen content in ethanol significantly improved the indicated thermal efficiency (ITE) through enhanced combustion, its lower viscosity simultaneously led to increased frictional losses.
Keywords: Biodiesel Production and Applications; Advanced Combustion Engine Technologies; Lubricants and Their Additives